ANALISIS KEKUATAN PERJANJIAN NOMINEE SAHAM DALAM PERSEROAN TERBATAS PENANAMAN MODAL ASING (PT.PMA) - Triwis, Sigit Teteki (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
The use of nominee shares through nominee shares agreement has grown and developed well in the investing world, especially within the investors who establish PT. PMA. In short, the concept of nominee shares are done by both localand foreign investors. One of the causes of the nominee shares usageis because there is no rules in the Company Law that regulate, prohibit, and unequivocally ban the nominee shares by making the stock agreement. The law of prohibition to make nominee shares agreement or stock statement can only be found in the Capital Market Law, Article 33 paragraph (1) and paragraph (2). This research is a normative legal research that moves from the void norm within our laws. The approach used in this study is the legislation and analytic approach. The legal materials in this study are taken from the primary materials, secondary legal materials, and tertiary legal materials. The results of this study indicate the cause of the nominee shares usage by making nominee stock agreement, has already stated in the Company Law. However, it only explainsthe requirement that the PT has to be founded by two (2) or more persons, it does not give any detail requirements of how to be the shareholders. Other than to fill the Company Law, by filling the requirement of the PT establishment,the use of nominee agreement is due to the restriction of the line business for PT. PMA. The void of the norm has resulted in the violation within the limited liability company, in which one of the shareholders in PT. PMA is not the actual owner or nominee, but only the registered owner from certain number of shares. The law of prohibition of nominee shares in UUPM is considered inefficient because there is no strict regulations and prohibitions in the Company Law, thus, in practice, the use of nominee shares by making the nominee shares agreementgrows and develops through the simulation or indirect agreement, known as the arrangement agreement.
Keywords: Nominee Shares Agreement, Limited Liability Company, Foreign Direct Investment